Anatomical Pathology, Behavioral, and Physiological Responses Induced by Application of Non-penetrating Captive Bolt Devices in Layer Chickens - Bandara, Rathnayaka Mudiyanselage Amila Subhashinie; Torrey, Stephanie; Turner, Patricia V.; Schwean-Lardner, Karen; Widowski, Tina M. (Frontiers in Veterinary Science, 2019)
We evaluated three models of non-penetrating captive bolt devices, Zephyr-E, Zephyr- EXL and Turkey euthanasia device (TED) for time to loss of sensibility and degree of brain damage during euthanasia in four age groups of male and female layer chickens (10-11, 20-21, 30-35, 60-70 weeks respectively). Latencies to onset of insensibility and cardiac arrest were assessed to detect whether bird euthanasia via these devices was humane and effective. Both gross and microscopic pathology evaluations were conducted to score skull and brain trauma post mortem. Insensibility was observed immediately after device application as determined by loss of pupillary light and nictitating membrane reflexes in all birds. Latencies to loss of jaw tone and neck muscle tone were longer in 60-70 weeks old roosters (p<0.05). Younger birds (10-21 week-old) demonstrated the longest time (p<0.0001) to onset of tonic convulsions, time at last movement, cloacal relaxation and cessation of heart beat. A positive correlation (p<0.0001) was found for all three devices in between time of cardiac arrest and behaviors of onset of tonic convulsions, last movement, and cloacal relaxation. More than 80% of birds had skin lacerations with external bleeding following application of all 3 devices. Device type did not affect the incidence of skull fractures but higher skull fracture scores were noted in 10-11 week-old birds compared to other ages. Regardless of device type and age, microscopic SDH was most apparent in the brain and proximal spinal cord of all birds. In summary, all three devices caused significant trauma to the midbrain and spinal cord. Results demonstrated that all three devices induce immediate insensibility after application and result in a humane death in all age groups of layer chickens.